KARAKTERISTIK KATARAK PADA DIABETES MELITUS DI RSUP DR. M DJAMIL PERIODE 2020-2021 - Nada Shafa Salsabila; Kemala Sayuti; Rahmi Lestari; Rudy Afriant; Hendriati Hendriati; Yustini Alioes (SINERGI : Jurnal Riset Ilmiah, 2026)
Cataracts are a condition in which the normally clear and clear lens of the eye turns cloudy. Cataracts that occur due to disorders of the endocrine system are caused by diabetes mellitus. This study aims to determine the characteristics of cataracts in diabetes mellitus at RSUP Dr. M Djamil Padang Period 2020 –2021. This research was a retrospective descriptive study with a cross-sectional approach to determine the characteristics of cataracts in patients with diabetes mellitus at RSUP Dr. M Djamil for the period 2020 - 2021. This study used secondary data in the form of medical records from 39 cataract patients with a history of diabetes mellitus. Data analysis was carried out in the form of descriptive analysis using the SPSS application. This study showed that 28 people (71.8%) respondents aged ≥ 60 years, 24 people were male (61.5%), 30 patients with duration of diabetes mellitus ≥5 years (76.9%), 19 respondents (48.7%) had mature cataracts. Individuals aged ≥ 60 years mostly had mature cataracts (14 people; 50.0%), male respondents mostly had mature cataracts (12 people; 50.0%) and individuals with cataract duration ≥ 5 years mostly had mature cataracts (17 people; 56.7%). The conclusion of this study is the discovery of cataracts in diabetes mellitus with the most age ≥ 60 years, male gender, duration of diabetes mellitus ≥5 years, and type of mature cataract. Most mature cataracts were found at age ≥ 60 years, male gender, and duration of diabetes mellitus ≥5 years.